MEDIA SOSIAL: ANTARA KEBEBASAN DAN EKSPLOITASI - Karman Karman (BPSDMP Kominfo Jakarta, 2014)
ABSTRACTCommunication technology has contributed to any social change, from printing press, to internet which include social media. The Internet presence plays an important role in social events such as Revolution in Egypt, Arabic Spring in Middle east. In Indonesia, social media creates social cohesion as seen in the conflict between Corruption Eradication Commission of Indonesia (KPK) versus National Police or case of